Social Support and Self Management Predict Academic Burnout Among Final Year Students: Dukungan Sosial dan Pengelolaan Diri Menjadi Faktor Penentu Terjadinya Kelelahan Akademik di Kalangan Mahasiswa Tingkat Akhir - Dyah Tri Meilani; Ghozali Rusyid Affandi (Psikologia : Jurnal Psikologi, 2026)
General Background: Academic burnout has become a significant concern among final year university students due to increasing academic demands, thesis completion, and psychological pressure during the transition toward graduation. Specific Background: Previous studies have identified social support and self-management as important factors associated with academic burnout, particularly among university students facing prolonged academic stress. Knowledge Gap: However, limited studies have simultaneously examined the contribution of social support and self-management to academic burnout among final year students in the Indonesian higher education context. Aims: This study aimed to examine the relationship between social support, self-management, and academic burnout among final year students at a university in Sidoarjo, Indonesia. Results: This quantitative correlational study involved 322 respondents selected using quota sampling. Data were collected using the Academic Burnout Scale, Multidimensional Scale of Perceived Social Support, and Self-Management Scale, then analyzed using multiple linear regression. The findings showed that social support and self-management jointly contributed 16.3% to academic burnout. Social support demonstrated a significant negative relationship with academic burnout (r = -0.311, p < 0.001), while self-management also showed a significant negative relationship (r = -0.353, p < 0.001). Novelty: This study simultaneously positions social support as an external factor and self-management as an internal factor in predicting academic burnout among final year students. Implications: The findings highlight the importance of strengthening academic counseling, social support systems, and self-management training programs to reduce academic burnout among university students.Highlights: Higher peer and family assistance was associated with lower emotional exhaustion among undergraduate respondents. Personal regulation skills showed stronger predictive value for reduced learning fatigue during thesis completion. Combined psychological and environmental factors explained 16.3% of student burnout variance. Keywords: Academic Burnout; Social Support; Self-Management; Final Year Students; University Students